Salivary Lactate Dehydrogenase Level: A Prognostic Biomarker for Oral Potentially Malignant Disorders - Jigna Shah; Kinjal Joshi (Indian Journal of Dental Research)
Aim: The study aims to evaluate salivary lactate dehydrogenase (LDH) levels in tobacco users (smoking and/or smokeless) with or without oral potentially malignant diseases (OPMDs), considering into factors like type of habit, duration, and frequency of use. Materials and Methods: The study included 60 patients in all, including those who used smokeless tobacco, smoked tobacco, and mixed tobacco and the control group. 1 mL of entire unstimulated saliva was collected using the spit technique and analysed using a semi-autoanalyzer to determine the mean salivary LDH levels. Result: The mean salivary LDH level in the control group was lower (128.31) than in the study group. A highly significant (P = 0.000) relationship was discovered between the groups and salivary LDH levels. There was no significant relationship (P > 0.005) between type of habit and mean salivary LDH level. A very significant result was found between the duration of habit in the smoking group (P = 0.000) and the frequency of habit in the smokeless group (P = 0.005). Conclusion: Saliva is a biochemical tool that may be easily used in diagnostic methods for mass screening. Mean salivary LDH levels are important for informing patients and increasing awareness about the shift from normal to OPMDs.